Recent Progress in Long-term Stability of Perovskite Solar Cells - Seyedali Emami; Luísa Andrade; Adélio Mendes (U.Porto Journal of Engineering, 2015)
Perovskite solar cells made a huge breakthrough among the nanostructured thin film photovoltaics. They exhibited certified power conversion efficiency (PCE) as high 24 % in 2015. A vast amount of research were spent on improvement of PCE and lowering the fabrication process temperature, resulting in outstanding outcomes in these areas. In contrast, the long-term stability and commercialization of these devices were not well studied. The review briefly summaries the challenges of perovskite solar cells in the road of stabilization and commercialization.